Testosterone and lean mass show a positive correlation with the technical performance of footballers - Felisberto, Pedro [UNESP]; Seidinger, Sylvia C. [UNESP]; Santos, Thaislaine [UNESP]; Torres, Wesley [UNESP]; Lira, Fabio S. [UNESP]; Buonani, Camila [UNESP] (Edizioni Minerva Medica, 2022)
BACKGROUND: Monitoring technical performance during a soccer match has become an indispensable practice, since the players perform different functions within the tactical system adopted by the team, resulting in specific technical actions that are fully responsive to the individual technical level of each player. Thus, current study aimed to investigate the possible direct and mediating relationship between salivary testosterone and the technical performance of semi-professional footballers during a training game. METHODS: To characterize the sample, the anthropometric profile, body composition, biological maturation, lower limb power, speed, estimation of maximum oxygen consumption, and physical performance were used. To determine testosterone concentrations, saliva was collected before and after the training game, for subsequent measurement using enzyme immunoassay (ELISA) and Salimetrics Kits. For quantification of technical performance and participation with the ball during the training game, scout software was used from the footage of the training game. The reliability of the technical performance analyses was determined through the repetition test of two attempts (Cohen's Kappa agreement index). RESULTS: The direct relationship between postgame testosterone and total participation with the ball in the second half; the direct relationship between the percentage of lean mass with postgame testosterone and an apparent relationship between percentage of lean mass and total participation with the ball from the set of relations mediated by postgame testosterone concentrations. CONCLUSIONS: The results suggest that testosterone concentrations combined with high levels of lean mass may have an important role in the technical performance and participation with the ball of semi-professional footballers.
Keywords: Athletic performance; Team Sports; Testosterone